1982
DOI: 10.1084/jem.156.4.1274
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of mitogenic responsiveness by nonresponding lymphocytes upon insertion of appropriate membrane components.

Abstract: Although the detailed mechanism of lymphocyte activation by polyclonal mitogens is far from understood, it is well established that the binding of the mitogen to the cell surface is essential for stimulation to occur (1, 2). Binding by itself is not sufficient to cause cell stimulation, as some lectins (e.g., from Helix pomatia) bind to lymphocytes and do not stimulate them (3), whereas others (e.g., concanavalin A [Con A] and the lectin: fro~ Phaseolus vulgaris and Lens culinaris) bind equally well to both T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The Lps gene may regulate the expression of some membrane component that recognizes LPS and there is some evidence to support this hypothesis. Studies using the cell fusion technique have shown that the expression of a genetic defect in C3H/HeJ mice is located on the membrane fraction and not in the nucleus (10,30). However, a number of studies on the binding of LPS to cells have not shown a difference between LPS-responsiveness and nonresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The Lps gene may regulate the expression of some membrane component that recognizes LPS and there is some evidence to support this hypothesis. Studies using the cell fusion technique have shown that the expression of a genetic defect in C3H/HeJ mice is located on the membrane fraction and not in the nucleus (10,30). However, a number of studies on the binding of LPS to cells have not shown a difference between LPS-responsiveness and nonresponsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We used the method described by Jakobovits et al [27] to insert PHA receptors into purified B lymphocytes. Vesicles made of PC/PS were prepared by dialysis of a detergent (DTAB) solution containing affinity-purified porcine PHA receptors and Sendai virus fusogenic HN and F proteins.…”
Section: Assay Of Reconstituted B Lymphocytesmentioning
confidence: 99%
“…A rabbit serum raised against LPS-responsive B cells, and absorbed with C3H/HeJ cells, was able to compete with endotoxin for binding on LPS-responsive B cells, and to inhibit their mitogenic response [6]. Furthermore, Jakobovits et al [7] were able partially to reconstitute LPS responsiveness in C3H/HeJ B lymphocytes by fusing them with plasma membranes from syngeneic LPS-responder B cells. These data suggested the existence of a cell-surface signaling receptor.…”
Section: Introductionmentioning
confidence: 99%